Nienależyte umocowanie pełnomocnika jako przesłanka nieważności postępowania - Barańska, Anna Maria (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The paper covers a nullity of the proceedings arising out of case where the representative of a party was not duly empowered within the meaning of the article 379 point 2. and the article 401 point 2. of the Polish Code of Civil Procedure. In practice this premise causes a lot of difficulties due to missing law permitting straight approval of procedural actions performed by a representative improperly empowered — having considered that categorical rejection of such an opportunity not always seems to be the right and justified decision. In the contents of the paper attention is paid to the fact that it is incorrect to equate the case in which a person was not able to perform as a proxy with the situation where the representative was improperly empowered. The first case entails the invalidity of the proceedings, while the latter may be subject to legitimization, as a result of a subsequent confirmation of the procedural actions taken by an empowered person. Finally, the issue of the admissibility of reporting such a violation by a party to the proceedings as well as their legal interest in such an action is raised. Such an analysis will permit to indicate the differences between cases along with an attempt to indicate a possible procedure when it occurs.
Keywords: proxy; nullity of the proceeding; art. 379 of the Polish Code of Civil Procedure; improper empower